2018
DOI: 10.1016/j.csl.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Learning static spectral weightings for speech intelligibility enhancement in noise

Abstract: Near-end speech enhancement works by modifying speech prior to presentation in a noisy environment, typically operating under a constraint of limited or no increase in speech level. One issue is the extent to which near-end enhancement techniques require detailed estimates of the masking environment to function effectively. The current study investigated speech modification strategies based on reallocating energy statically across the spectrum using masker-specific spectral weightings. Weighting patterns were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 46 publications
3
25
0
Order By: Relevance
“…It was found that, regardless of the masker type, the suggested weightings always tend to sparsely boost some of the frequencies above 1000 Hz by approximately 10 dB, although the patterns vary in details across maskers. Another attempt was made using a different optimisation algorithm and objective metric in [21]. A similar boosting pattern was observed, but with a boosting amount of 30 dB.…”
Section: Speech Modification Algorithmsmentioning
confidence: 52%
See 4 more Smart Citations
“…It was found that, regardless of the masker type, the suggested weightings always tend to sparsely boost some of the frequencies above 1000 Hz by approximately 10 dB, although the patterns vary in details across maskers. Another attempt was made using a different optimisation algorithm and objective metric in [21]. A similar boosting pattern was observed, but with a boosting amount of 30 dB.…”
Section: Speech Modification Algorithmsmentioning
confidence: 52%
“…After energy renormalisation, the speech energy is effectively transferred to the boosted regions from elsewhere. Further evaluation confirmed that ConstBoost can be as or almost as effective as the noise-and level-dependent spectral weighting in the tested conditions [21]. Figure 1 shows examples of long term average spectra of speech uttered by a male talker, unmodified and spectrally-modified (no DRC applied) by the algorithms introduced above.…”
Section: Speech Modification Algorithmsmentioning
confidence: 58%
See 3 more Smart Citations